Factors Affecting Students Performance – Time Management - Razak, Firdaus (Journal of Computing Technologies and Creative Content, 2019)
A study was carried out to examine the perceptions and preferences of students on how they manage their time while on study. This study focused on for finding factors influencing student’s preferences. Overall a set of 16 question questionnaires were distributed to 100 students for conducted a research to investigate the factor that effect on how the student manage their time. Consequently, UNIKL MIIT and UKM students as respondents been used to identify the factors that affect their time. This study revealed positive aspects is needed for students to be able choose the best way to manage their time to study.